Is There a Role for Transplantation in Gynecologic Oncology?: Autotransplantation and Other Lessons. Issue 3 (1st March 2013) - Saso, Srdjan; Hamed, Ali Hassan; Doctor, Cyrus; Thum, Meen-Yau; Naji, Osama; Smith, James Richard; Vianna, Rodrigo; Del Priore, Giuseppe
Abstract : Abstract: We describe an exciting and novel surgical option, which may be used to treat formerly unresectable masses. This process is commonly referred to as autotransplantation (AuTn), and it combines the advances in transplant medicine and applies them to surgical oncology. The idea behind AuTn is the removal of the cancerous organ(s) to allow complete anatomic resection of the tumor mass, with consequent anastomotic reimplantation or AuTn of the now macroscopically tumor-free organ back into the patient. Autotransplantation has been used to remove large fibromatosis and desmoid tumors as well as malignant tumors. Our belief is that using lessons learned from the field of transplantation, AuTn can be applied in gynecologic oncology.